ONLINE NEWSPAPER COVERAGE OF CEREMONIES COMMEMORATING NGUYEN DU’S DEATH - Lê Phong Lê (Tạp chí Khoa học Đại học Đà Lạt)
A series of activities were held in 2020 to commemorate the 200th anniversary of Nguyen Du’s death. This paper analyzes the recent coverage by media and communications about the commemoration ceremonies and provides an evaluation of the advantages and limitations of promoting a cultural event in Vietnamese online newspapers. This paper examines topics, types, forms, feedback, tags, and info boxes on four websites: Tuoi Tre online, VnExpress, Zing News, and Ha Tinh online from June to October 2020.